Software fortresses : modeling enterpise architectures - Sessions, Roger, 1896-1985 (Addison-Wesley, 2003)
This book introduces a new approach for modeling large enterprise systems: the software fortress model. In the software fortress model, an enterprise architecture is viewed as a series of self-contained, mutually suspicious, marginally cooperating software fortresses interacting with each other through carefully crafted and meticulously managed treaty relationships. The software fortress model is an intuitive, simple, expressive approach that maps readily to existing technologies such as .NET and Java 2 Enterprise Edition (J2EE). This book is designed to meet an immediate need to define, clarify, and explain the basics of this new modeling methodology for large enterprise software architectures. Software Fortresses is your essential roadmap to all aspects of software fortresses. Key topics include: The fundamental concepts and terminology of software fortresses Documentation techniques, including Fortress Ally Responsibility Cards (based on Class Responsibility Cards) and Sequence Ally Diagrams (based on UML's Class Sequence Diagrams) The proper use of drawbridges to provide fortress interoperability The innovative software fortress model for enterprise security Correct design approaches to fortress walls, which keep intruders out, and to guards, which let allies inches The role of loosely coupled and tightly coupled transactions in a software fortress architecture Design and technology issues associated with the six major software fortress types This book is a must-read for all enterprise software professionals, whether you are a manager seeking to rein in run-away enterprise system complexity, an architect seeking to design interoperable, scalable, and highly secure systems, a consultant expected to give advice on how .NET and J2EE fit into the enterprise space, an implementer wanting to understand how your system relates to a larger enterprise architecture, or a business analyst needing to know that your system requirements will be translated into a successful software implementation. 0321166086B12202002.